Principal Conversation and Teacher Vitality: An Empirical Analysis in Low-Performing Schools - Adams, Curt; Hamlin, Daniel; Adigun, Olajumoke (International Journal of Education Policy and Leadership, 2024)
This article draws on a teacher survey (n = 789) to examine the relationship between teacher vitality and two conversational approaches—transformative leadership conversation and controlling conversation. The analyses use latent structural equation modelling. The sample is restricted to teachers in schools with an accountability rating of “low performing” so that principal/teacher conversations can be examined in schools that potentially have the most to gain from strong teacher vitality. Results indicate that the use of transformative leadership conversation had a direct positive relationship with teacher vitality (β = .26) and an indirect relationship (β = .22) with it through teacher need satisfaction. Controlling conversation had a negative relationship with teacher vitality, but it did not have a statistically significant relationship with need satisfaction.